Formulation Of Liquid Soap Based on Sea Grass (Eucheuma Cottonii) Used Olive Oil as An Oil Phase - In Rahmi Fatria Fajar; Dewi Rahma Fitri; Roikhatun Roikhatun; Delviza Syari (SANITAS: Jurnal Teknologi dan Seni Kesehatan, 2022)
The potential of Indonesian marine biota products is very large to be processed into commercial commodities. One of them is seaweed Eucheuma cottonii which contains phenolic profiles, vitamin A, vitamin C, vitamin E and various minerals that play a role in healing and rejuvenating the skin. This liquid soap product contains the main ingredients of Eucheuma cottonii seaweed pulp and an olive oil soap base. Olive oil has a high content of oleic acid which is often used as a good antioxidant and moisturizing agent in the field of cosmetics. Objective to obtain a liquid bath soap formulation with the active ingredient of Eucheuma cottonii seaweed pulp using optimization of olive oil as an oil phase. Testing seaweed includes moisture content, ash content, content fat, protein content and heavy metal contamination. The method of making Eucheuma cottonii seaweed pulp is by blanching seaweed, soaking in 1:10 deonize water for 12 hours, draining, then homogenizing it with deonize water 1:2 for 3 minutes. The seaweed pulp is then formulated into liquid bath soap with the optimization of the best olive oil formula. The results showed that seaweed had 22.27% water content, 29.55% ash content, 0.53% fat content, 5.89% protein content and Pb < 0.25; Hg<0.1. Seaweed slurry obtained a clear mass and expands and can be used as a gelling agent. The soap formula obtained specific gravity 1.0894-1.1206 g / ml, pH value at range 6.26-6.43, viscosity in the number 420 cp - 2,800 cp and all preparations are physically and chemically stable during storage. Conclusion Eucheuma cottonii seaweed porridge can be formulated into soap and meets the requirements of liquid soap